Etika Bermedia Sosial dalam Perspektif Mazhab Fikih: Studi Komparatif Antara Mazhab Syafi’i dan Mazhab Hanbali - Maritza Verda Tsary; Ramadhan Bayu Giriansyah; Eka Putri Febryani; Friend Jaya Sahaja; Siyono (Scientific Journal for Nation Building, 2026)
The rapid development of digital media has significantly transformed patterns of communication, enabling instantaneous interaction without spatial or temporal limitations. However, this transformation has also generated ethical challenges, including the spread of misinformation, cyberbullying, hate speech, and violations of personal privacy, which increasingly undermine social harmony and moral responsibility. This article aims to analyze Islamic media ethics through the perspectives of the Shafi‘i and Hanbali schools of jurisprudence, focusing on communication, publication, and privacy in the digital sphere. Employing a qualitative normative approach, this study utilizes library research by examining classical fiqh texts, contemporary scholarly works, and relevant fatwas to construct a comparative analysis grounded in fiqh al-mu‘amalah and maqāṣid al-sharī‘ah. The findings reveal that both schools emphasize ethical communication rooted in truthfulness, protection of honor, and prevention of social harm. The Shafi‘i school prioritizes public welfare (maṣlaḥah ‘āmmah) and the prohibition of violating others’ rights through harmful speech or information disclosure, while the Hanbali school places stronger emphasis on tabayyun (verification), caution, and the avoidance of exposing private matters. Despite differences in emphasis, both schools converge on the obligation to prevent harm, safeguard dignity, and uphold moral responsibility in digital interactions. This study concludes that integrating Shafi‘i and Hanbali ethical frameworks provides a comprehensive Islamic model for ethical social media conduct, contributing to the development of normative Islamic discourse on digital ethics and offering practical guidance for contemporary Muslim societies.